Strategien biotechnischer Innovation. Analysen, Konzepte und empirische Befunde - Feuerstein, Günter (Hamburg University Press, 2007)
Over the past decade, efforts been have intensified to establish a viable location for modern biotechnologies in the Hamburg region. The growing intensity of Hamburg's biotechnological support can be seen as a reflection on the drastic slump of newly founded biotechnology companies that took place in previous years. Numerous companies disappeared from the scene after a short period of time despite good concepts and good technologies. Against this background the lecture series "Strategies of Biotechnological Innovation" was held in the winter semester 2004/2005 at the Research Center for Biotechnology, Society and Environment (BIOGUM) of the University of Hamburg. Its aim was to examine the possibilities, problems and limitations of innovation management from different perspectives. The texts of this volume are based on lectures given by the contributors in the context of this lecture series.